2023
DOI: 10.3390/pr11010276
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Annona muricata Linn Fruit Pulp Lyophilized Powder against Paracetamol-Induced Redox Imbalance and Hepatotoxicity in Rats

Abstract: In the current investigation, Annona muricata Linn. lyophilized fruit pulp powder was evaluated for its hepatoprotective activity induced by paracetamol or acetaminophen (APAP). Male Sprague Dawley rats were orally pre-treated for 15 days with A. muricata lyophilized fruit pulp powder at low (1 g/kg b.wt) and high doses (2 g/kg b.wt). Silymarin (100 mg/kg) was administered as the standard drug. Hepatotoxicity was induced using APAP, in a single oral administration of 2.5 g/kg body weight dosage on the 15th day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…The elevation levels of ALT and AST in EAC tumorbearing mice is an index of deterioration of hepatic functions due to cancer proliferation as observed in the EAC group and it suggested a functional impairment of hepatic cell membranes and a cellular leakage which demonstrated that EAC-induced liver injury [38]. Previous studies reported the ameliorative effect of Graviola (A. muricata) on hepatic injury in experimental animals due to their antioxidant, apoptotic, and anti-inflammatory efficacies [39,40]. In the present study, the protective and antitumor effects of ASFE were investigated in EAC-bearing mice.…”
Section: Discussionmentioning
confidence: 92%
“…The elevation levels of ALT and AST in EAC tumorbearing mice is an index of deterioration of hepatic functions due to cancer proliferation as observed in the EAC group and it suggested a functional impairment of hepatic cell membranes and a cellular leakage which demonstrated that EAC-induced liver injury [38]. Previous studies reported the ameliorative effect of Graviola (A. muricata) on hepatic injury in experimental animals due to their antioxidant, apoptotic, and anti-inflammatory efficacies [39,40]. In the present study, the protective and antitumor effects of ASFE were investigated in EAC-bearing mice.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, an increase in superoxide dismutase, catalase, glutathione peroxidase, and glutathione S-transferase enzyme levels was reported. Similarly, Zakaria et al [81] and Menon et al [82] investigated the hepatoprotective property against paracetamol of Dicranopteris linearis leaf extract, and Annona muricata fruit pulp lyophilized powder was noteworthy.…”
Section: Discussionmentioning
confidence: 99%